2012
DOI: 10.1177/1091142112442742
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cigarette Taxation on Prices

Abstract: This article combines new, author-collected tax data with data both from the American Chamber of Commerce Researchers Association cost of living index and from the Tax Burden on Tobacco to measure the relative effects of city, county, and state excise cigarette taxation on cigarette prices. The results indicate that a $1 increase in the state excise cigarette tax increases cigarette prices between $1.10 and $1.14, but that a $1 increase in a city- or county-level excise tax increases prices by $1.07. These fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Price was non-linear over time and a dummy coding approach is consistent with the modeling approach of other studies [5,7,10]. For the smoking prevalence model, smoking was only somewhat non-linear thus, main results are reported using a more parsimonious model that included linear time + quadratic time + dummy variable for federal cigarette tax.…”
Section: Methodssupporting
confidence: 65%
See 2 more Smart Citations
“…Price was non-linear over time and a dummy coding approach is consistent with the modeling approach of other studies [5,7,10]. For the smoking prevalence model, smoking was only somewhat non-linear thus, main results are reported using a more parsimonious model that included linear time + quadratic time + dummy variable for federal cigarette tax.…”
Section: Methodssupporting
confidence: 65%
“…Harding (2012) used a shorter time period and found a pass-through of approximately 0.85 among a household panel and Chiou (2014) used data from supermarkets in a single municipality (the Chicago area) and found an average pass-through of 0.80 [5,28]. Other studies that reported taxes were fully passed or over-shifted onto consumers while using data from supermarkets only or fewer municipalities or price data from individual self-reports [4,8,9,10] Advantages of the dataset we used over other studies were: use of prices of specific goods rather than average price paid which may reflect substitution; included many more years of data relative [4,7,8] and offered better spatial resolution [9,10]. Our findings suggest that cigarette price varied by SES but the variation was small and in general, state cigarette taxes were equitably passed to consumers as there was no evidence that associations between state excise tax and price were different based on area-level SES or minority composition of residents near the chain stores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15] Most of these studies find that excise taxes are overshifted. Our results are more nuanced.…”
Section: Discussionmentioning
confidence: 99%
“…South Africa is an important example for other countries, since it was one of the first middle-income countries to use excise tax increases as a tobacco control tool. The paper adds to the literature on excise tax pass-through, [9][10][11][12][13][14][15] but, crucially, considers a structural break in the industry's pricing reaction to excise tax increases.…”
Section: Introductionmentioning
confidence: 99%